Stres Kerja, Dukungan Keluarga, Work-Family Conflict Dengan Work-Life Balance, Work Stress, Support Family, And Work-Family Conflict With Work-Life Balance - Sedjati, Wahyu Widiatmoko; Widhiastuti, Hardani; Nusandari, Arumwardhani; Yuli Budiati (Reswara Journal of Psychology, 2023)
Involvement women in public sector currently increasing various fields work professions, such conditions certainly require a balance work and family life. There several factors affect work-life balance such as work stress, family support and family and work conflicts in a person. Low work-life balance in a career woman can result her not being able to carry out her role as a job and housewife properly so that work-life balance becomes important for all workers, including Kendall Police. Study aims to empirically examine effect work stress, family support and family and work conflict on work-life balance in Kendal Police women who married or have families. Temporary hypothesis that there is a positive and significant influence between work stress, family support, and family and work conflict on work-life balance in female police officers in Kendal Police station. Results study show that work stress partially affects work-life balance. Family support has no partial effect on work-life balance. Simultaneously family support has no effect on work balance through family and work conflict. Partially work stress affects work-life balance through family and work conflicts in Police Women of Kendal Police.Keywords: Work-Life Balance, Work-Family Conflict, Work Stress, Support Family.